Phosphate sorption by active acid sulfate soils of Peninsular Malaysia - J. A., Ogunwale; Jusop, Shamsuddin (Universiti Putra Malaysia Press, 1999)
Phosphate sorption data of four soil samples representing two soil series (Sedu and lawa Series; both Typic Sulfaquepts) from Peninsular Malaysia were described by the Langmuir II sorption model. Lim Chin, Raja Muda and Kuala Linggi soils represent Sedu series, while the soil sample from Serkat represent Jawa Series. The phosphate sorbed by the four soil samples conformed to the Langmuir II adsorption isotherm. Lim Chin and Raja Muda estate soils have r values of 0.98 and 0.99, respectively, while Serkat and Kuala Linggi soils have r values of 0.96 and 0.95, respectively. Phosphate adsorption maxima and buffer capacities were higher in the Sedu soils (Lim Chin and Raja Muda Estate) than in Jawa (Serkat) and the Sedu soil (Kuala Linggi). Liming of the Sedu Soil (Raja Muda Estate) and Jawa soil (Serkat) at 1 t ha- I reduced phosphate sorbed by 3.1 and 13.1 percent, respectively. Rates greater than 2 t ha-J of lime increased the P sorptive capacities of the soils.